THE INFLUENCE OF BUSINESS RISK PROFITABILITY AND DIVIDEND POLICY ON COMPANY VALUE IN THE COMPANY REGISTERED FOOD AND DRINK - Brigita Abigail Tri Ayu Ningrum Hutabarat; Angelyn Prily Zefanya Sihite; Herlita Helsyafira Br Tarigan; Jholant Bringg Luck Amelia Br Sinaga; Windi Astuti (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Background : This study aims to examine Business Risk, Profitability and Dividend Policy on Firm Value in food and beverage companies listed on the IDX. Sample selection was done by purposive sampling method. The sample used is companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) in 2019-2021 as many as 14 companies with the amount of data processed for 3 years as many as 42 companies. Method : The type of data used is secondary data obtained from the official IDX website in the form of company financial reports. The data analysis tool used is multiple linear regression with the help of the SPSS version 20.0 program. Result :The results of this study indicate that partially Profitability (ROA) and Dividend Policy (ROA) have an effect and are significant on Firm Value, while Business Risk has no effect and is not significant for Value. Company. Then simultaneously Business Risk, Profitability (ROA) and Dividend Policy (ROA) have a significant and significant effect on Company Value. Conclusion: The magnitude of the influence of Business Risk, Profitability (ROA) and Dividend Policy (ROA) is used in the research model on Firm Value. is 39.1%. while the remaining 60.9% is explained by other factors not examined in the study.